Oncolytic virus: A catalyst for the treatment of gastric cancer - Wang, Junqing; Du, Linyong; Chen, Xiangjian (Frontiers in Oncology, 2022)
Gastric cancer (GC) is a leading contributor to global cancer incidence and mortality. According to the GLOBOCAN 2020 estimates of incidence and mortality for 36 cancers in 185 countries produced by the International Agency for Research on Cancer (IARC), GC ranks fifth and fourth, respectively, and seriously threatens the survival and health of people all over the world. Therefore, how to effectively treat GC has become an urgent problem for medical personnel and scientific workers at this stage. Due to the unobvious early symptoms and the influence of some adverse factors such as tumor heterogeneity and low immunogenicity, patients with advanced gastric cancer (AGC) cannot benefit significantly from treatments such as radical surgical resection, radiotherapy, chemotherapy, and targeted therapy. As an emerging cancer immunotherapy, oncolytic virotherapies (OVTs) can not only selectively lyse cancer cells, but also induce a systemic antitumor immune response. This unique ability to turn unresponsive ‘cold’ tumors into responsive ‘hot’ tumors gives them great potential in GC therapy. This review integrates most experimental studies and clinical trials of various oncolytic viruses (OVs) in the diagnosis and treatment of GC. It also exhaustively introduces the concrete mechanism of invading GC cells and the viral genome composition of adenovirus and herpes simplex virus type 1 (HSV-1). At the end of the article, some prospects are put forward to determine the developmental directions of OVTs for GC in the future.